A framework for applying learning analytics in serious games for people with intellectual disabilities. (30th July 2018) - Nguyen, Andy; Gardner, Lesley A.; Sheridan, Don
Abstract: This paper proposes a systematic framework to integrate learning analytics into serious games for people with intellectual disabilities. Serious games for an inclusive learning environment need to be prudently designed with adaptive and measurable competencies to meet the needs of the target users. The recent emergence of learning analytics provides a capability to capture important data in real time from within the highly interactive nature of serious games to better understand and enhance the learning process. Although previous research has addressed different applications of learning analytics in serious games, few studies have investigated the needs of individuals with disabilities. This paper proposes a framework for serious games analytics specialised for people with intellectual disabilities (SGAPID) for the purpose of supporting the integration of learning analytics within serious games to create an inclusive learning environment. We provide a framework based on previous studies in both learning analytics, serious games and educational technologies for people with intellectual disabilities. The framework consists of three central components, namely learner profiling, learning adaptation and learning evaluation. It provides needed guidance for educational application developers and reflects the contemporary trends in educational technologies. The SGAPID framework will also be valuable for the design, implementation, evaluation and adaptation of serious games for inclusive learning and teaching at the group or individual level.